A time-lagged study on the moderating role of overall satisfaction in perceived politics: Job outcomes relationships. (4th August 2016) - Jam, Farooq Ahmed; Donia, Magda B L; Raja, Usman; Ling, Chong Hui
Abstract: In a time-lagged study with independent measures ( N =115, paired responses), we examined the interactive effects of perceived organizational politics and overall satisfaction on job stress, interpersonal conflict, job performance, and creativity. The data were collected from a diverse sample of employees from various workplaces in Pakistan. The findings showed that perceived politics had a positive effect on job stress, while overall satisfaction had a negative effect on interpersonal conflict and a positive effect on creative performance. The results also revealed that in the face of high politics, highly satisfied individuals demonstrated higher levels of creativity and job performance. However, in this context of high politics negative effects were also observed, namely that highly satisfied individuals participated in interpersonal conflict and experienced high stress.